Comparison of operative 'difficulty' with post-operative sequelae in lower third molar surgery - Adekunle Adetayo; Modupe Adetayo; Mayowa Somoye; Michael Adeyemi (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2019)
Background: The outcome of studies on the effect of patients' factors, dental factors and operative factors on postoperative sequelae following surgical extraction of lower third molar have been unequivocal. Objective: To determine the effect of surgical difficulty (using Pederson's scale), Body Mass Index (BMI) and operative time on the extent of post-operative pain, swelling and trismus following third molar surgery. Methods: The study was a prospective analytical study of the effect of surgical difficulty, BMI, age and operative time - Total Intervention Time (TIT) - on the extent of post-operative pain, swelling and trismus. Eighty-four subjects with surgical extraction of impacted lower third molar were studied. All the subjects had a standard Peri-apical radiograph through which the difficulty index was calculated for all third molars using the Pederson scale. Anthropometric vertical and horizontal facial measurements and pain measurement were taken pre-operatively and post-operatively on days 1, 3, 5 and 7. Results: Of the 84 subjects, 16 (19%) were males, while 68 (81%) were females in the ratio of 1:4.2. BMI showed a positive correlation with all the three variables and was significant for swelling on the post-operative days assessed while TIT showed a negative correlation with most of the variables and was significant for trismus. Conclusion: This study showed that age and operative time might have an inverse relationship with the common post-operative complications after lower third molar surgery and BMI might influence the extent of these complications.